STUDI KARAKTERISTIK AIRFOIL NACA 2410 DAN NACA 0012 PADA BERBAGAI VARIASI ANGLE OF ATTACK - Sarjito, Sarjito (Media Mesin: Majalah Teknik Mesin, 2010)
In the past, for making and investigating performance of airfoil should be conducted by trial and error, and often a lot of materials waste. Since every time, if we would like to change of the model, we have to produce new model first for doing next investigation. Beside that, for testing the airfoil should be physically done in the wind tunnel, it is not very easy to get information of pressure and velocity distribution accurately. Now adays, it can be done computationally, faster and cheaper by using both of open sources and commercial software. The aim of this research is to investigate the characteristics of airfoil performance. It covers the pressure distribution, velocity around the airfoil, and visualization of trajectories. Comparison between symmetric airfoil NACA-0012 and asymmetric airfoil NACA2410 performance will be explained, especially relationship between CL, CD versus a computationally. Experiment is preceded by making of symmetric airfoil model as well as asymmetric airfoil model by using design foil open source software, and then for adjusting angle of attach was assisted by the AutoCAD software, after that, meshing and solving process to be done in the Solid Work Cosmos Flow software 2007. Analysis covers distribution of pressure, velocity and trajectories simulation. The result of the research shows, that increasing of angle of attach will be followed by increasing of lift coefficient polynomially, other than coefficient lift is drag coefficient which proportional with angle of attach. However, it can be seen that NACA-0012 has the higher coefficient of lift and drag coefficient than NACA-2410. These patterns has also be compared with U.S Department of Transportation Federal Aviation document, apparently there has similar trend each others